Peningkatan Keterampilan Membaca Pemahaman Peserta Didik menggunakan Model Cooperative Learning Tipe Think-Talk-Write (TTW) di Kelas V SD Negeri 05 Sarilamak Kabupaten Lima Puluh Kota - Akbar, Gilang Rayhan; Muhammadi, Muhammadi (TSAQOFAH, 2025)
This study was motivated by the low reading comprehension skills among fifth-grade students at SD Negeri 05 Sarilamak, characterized by teacher-centered learning and students’ difficulties in understanding texts, identifying main ideas, and analyzing key details. The aim of this research is to describe the improvement of reading comprehension skills through the implementation of the Cooperative Learning model, specifically the Think-Talk-Write (TTW) type. The study employed Classroom Action Research (CAR) conducted in two cycles, each comprising planning, implementation, observation, and reflection stages. The research involved 23 students and applied a combination of qualitative and quantitative approaches. The results demonstrated significant improvements from Cycle I to Cycle II: instructional material assessment increased from 85.71% to 96.42%, teacher-related aspects from 77.77% to 94.44%, and student-related aspects from 75% to 91.66%. Reading comprehension skills improved from 73.18% to 87.70%. These findings indicate that the TTW model effectively enhances students’ reading comprehension abilities. Therefore, this model is recommended as an effective alternative learning strategy to improve reading comprehension skills in elementary education.